Quantitative discrimination of normal fault segment growth and its geological significance: example from the Tanan Depression, Tamtsag Basin, Mongolia. Issue 5 (4th July 2018) - Wang, H. X.; Fu, X. F.; Liu, S. R.; Chu, R.; Liu, B.; Shi, P. P.
ABSTRACT: This work focuses on quantitative discrimination of fault segment growth and its effect on sedimentation and stratigraphic evolution in the Tanan Depression, the Tamtsag Basin, Mongolia. Integrated seismic data sets and stratigraphic data suggest that normal faults evolve as fault segments grow, link and amalgamate to form a larger fault. Three main stages in the evolution of fault zone are recorded in the syn-rift stratigraphy. This paper applies a method to effectively discriminate the locus of fault segments by 'three diagrams' and quantitatively reconstruct process of fault growth by the maximum throw subtraction method. Backstripped to T23 SB event, the F1 fault comprises four hard-linked segments, and the F2 fault is divided into four soft-linked segments (F2-4 and F2-5 segments are shown by hard linkage) at the T23 structural level. The F1 and F2 fault comprise hard-linked segments at the T23-1 structural level when the F1 and the F2 are backstripped to the T22 (133.9 Ma) SB event. The F1 fault is divided into three soft-linked segments (F1-2 and F1-3 segments are shown by hard linkage), and the F2 fault is divided into four isolated fault segments at the T23-1 structural level when the F1 and the F2 is backstripped to the T23 SB event. Incorporation of paleo-fault geometry, isochron thickness map and sedimentary facies suggest that the transfer zone provided accommodation space for sediment discharge and deposition, and the depocentres were formed at the locus of maximum throw along a fault segment during its overall deposition.